Nasr: A Product of Pakistan's Strategic Culture. (1st January 2016) - ,
Abstract : After the dismal failure of Operation Parakram, India went back to the drawing board and developed a new limited war strategy, referred to as the Cold Start Doctrine, with the aim of quick mobilization of their troops to Pakistan's border, from where they could launch conventional strikes against Pakistan and at the same time not escalate the conflict to full scale or to the nuclear level. In response to India's Cold Start Doctrine, Pakistan introduced tactical nuclear weapons. To understand why Pakistan developed the tactical nuclear weapons we must try to understand their strategic culture. The paper will argue that the Cold Start Doctrine is in fact real and can be materialized, and for that reason Pakistan has had to respond to the threat it poses. In this paper we will try to understand Pakistan's response to the Cold Start Doctrine by trying to grasp its strategic culture.